Mechanisms of aureobasidin A inhibition and drug resistance in a fungal IPC synthase complex - Xinyue Wu; Xin Gong; Tian Xie (Nature Communications)
Abstract The enzyme inositol phosphorylceramide (IPC) synthase is essential for survival and virulence in fungi, while absent in mammals, thus representing a potential target for antifungal treatments. Aureobasidin A (AbA), a natural cyclic peptide, displays antifungal activity and inhibits IPC synthase, but the precise molecular mechanism remains unclear. Here, we present the cryo-EM structure of the Saccharomyces cerevisiae IPC synthase, composed of catalytic subunit Aur1 and regulatory subunit Kei1, in its AbA-bound state. The complex is resolved as a dimer of Aur1-Kei1 heterodimers, with Aur1 mediating homodimerization. AbA occupies a predominantly hydrophobic pocket in the catalytic core domain of each Aur1 subunit, blocking the entry of both substrates. Mutations conferring AbA resistance cluster near the AbA-binding site, thus interfering with AbA binding. Our study lays a foundation for the development of therapeutic drugs targeting fungal IPC synthase.